Development of a Vitamin K Database for Commercially Available Food in Australia - Palmer, Claire R.; Koch, Henrietta; Shinde, Sujata; Blekkenhorst, Lauren C.; Lewis, Joshua R.; Croft, Kevin D.; Hodgson, Jonathan M.; Sim, Marc (Frontiers in Nutrition, 2021)
Vitamin K content of foods is known to vary substantially by geographical location. In Australia, no Vitamin K database of food exists, thereby creating ambiguity when trying to develop national dietary intake guidelines. This investigation aimed to develop a Vitamin K database for commonly consumed foods that are commercially available in Australian supermarkets. The Vitamin K1 (phylloquinone; PK) and K2 (menaquinone; MK4, MK7) content of 60 foods known to contain Vitamin K were assessed (e.g. vegetables fruits, oils, animal products, dairy and fermented foods). A liquid chromatography with tandem mass spectrometry (LCMS/MS) method was developed and used to measure PK and MKs in different foods with an improved chromatographic separation and detection of Vitamin K’s and their analogues. The LOD and LOQ for PK and MK4 was 0.1 ng/ml, 0.5 ng/ml and 0.5 ng/ml, 1.0 ng/ml, respectively. The majority foods contained detectable PK (53/60), about half contained MK4 (31/60), and few contained MK7 (3/60). PK was highest in green leafy vegetables, with moderate amounts in oils. Highest MK4 content was in chicken eggs and meat products such as ham and chicken. This database enables nutritional epidemiologist to estimate dietary Vitamin K intake, especially in Australian cohorts, for a range of health outcomes.